Quacks, Lemons, and Self-Regulation: A Welfare Analysis - Thomas Gehrig; Peter-J. Jost (Northwestern University, Kellogg School of Management, Center for Mathematical Studies in Economics and Management Science, 1993)
The paper provides a framework in which suppliers of experience goods find it in their best interest to provide and enforce quality standards. This self-regulatory outcome is compared to various forms of statutory regulation, such as price regulation and quality regulation. The comparision is attractive, since the suppliers can observe each others' product qulity at lower cost than customers or policy maker. As long as quality is the only variable unknown to consumers and policy makers, any self-regulatory outcome can be replicated by an appropriate statutory policy. However, when additional variables (such as cost parameters) are private information of the suppliers, self-regulation may be strictly socially desirable.
Keywords: 330